(untitled) (Research, Society and Development, 2021)
Physical therapy is the profession that, among many competencies and skills, aims to develop, maintain, and restore movement and functional capacity throughout life. The specialization in this profession has a great contribution and enhances the technical capacity and assertive decision making in what corresponds to the promotion, prevention and recovery of the health of their patients. In view of this, this study aimed to describe the specializations and specialties in physical therapy as strategies for training and professional qualification. A descriptive bibliographic review was carried out using the following databases as a source: SciELO, COFFITO, CREFITOS and Health Sciences Descriptors. The importance and contribution of the processes of specializations and specialties was observed for the formation and professional qualification of the physiotherapist, from the moment of reflecting on the specialty during graduation to the application of the knowledge and praxis in the day-to-day work of assistance or teaching acquired in the specializations. It was also observed which strategies and tools are used for training and improvement for the physical therapy professional. It is estimated that physical therapists seek more qualification either through Latu Sensu, Stricto Sensu specializations and/or Professional Specialty through qualification exams, so that they can act in a more precise way in the health-disease process of the population and improve their practice.